IMPLEMENTASI PERMAAFAN HAKIM (RECHTERLIJK PARDON) DALAM KUHP NASIONAL - Laksita, Doni (Cahaya Ilmu Bangsa, 2025)
This study seeks to examine the application of Judicial Pardon (Rechterlijk Pardon). The study's findings reveal a noticeable transition in the sentencing of offenders from initially retributive law enforcement to restorative justice. This is also reflected in the National Criminal Code as stated in Article 54 paragraph (2), which regulates that offenders who demonstrate a serious intention to change and take responsibility can receive pardon and be accepted back into society. However, its application must be carried out with careful thought and understanding. This is important to ensure that this authority does not undermine the dignity and honor of the judiciary, as well as to prevent potential abuses that may occur through practices of corruption, collusion, and nepotism. Considerations regarding the